تأثير نقع البذور بمنظمات النموّ في نموّ بادرات صنف القمح الطري شام6 تحت ظروف الإجهاد الملحي - ديب, طارق; سوسي, فاتن (Latakia University Journal -Biological Sciences Series, 2018)
تمّت دراسة تأثير نقع البذور بمنظمات نموّ النبات ( الكاينتين Kinetin وحمض الجبريليك GA3) في بزوغ بادرة صنف القمح الطري شام6 ونموّه تحت الظروف العادية (2.5 dS m-1) والظروف الملحية (dS m-1 12). بغية تحديد فائدة هذين المنظمين في زيادة التحّمل النسبي للملوحة. خلال اختبار البزوغ، تأثرت نسبة البزوغ النهائي ونسبة انخفاض البزوغ، والزمن الوسطي اللازم للبزوغ في معظم المعاملات الأولية Priming treatments قبل البذر. وازداد معنوياً طول الجذر، السويقة، الوزن الطري والجاف للبادرات المعاملة باﻠ (25ppm Kinetin) تحت الظروف العادية والملحيّة. خفضت مجمل معاملات نقع بذور الصنف شام6 بمنظمات النموّ، الناقلية الكهربائية (حتى بعد 12 ساعة نقع) مقارنةً بغير المعاملة بمنظمات نموّ. سبب نقع البذور باﻠ 25ppm Kinetin انخفاضاً أعظمياً في نسبة المواد الراشحة من البذرة، في حين لوحظت زيادة في الارتشاح الإلكتروليتي في المعاملاتppm GA3100, 50, 25. لذلك يمكن الاستنتاج بأن المعاملات الأولية خفّضت من تأثير ضرر الملوحة، لكن التحسّن كان أفضل مع معاملة 25ppm Kinetin، كما أظهرت النتائج المتعلقة بنموّ البادرة، زيادة الوزن الطري والجاف تحت الظروف العادية والملحية، في حين لم يكن نقع البذور باﻠ GA3 فعالاً في زيادة تحمّل الملوحة تحت الظروف التجريبية. The effects of seed soaking in plant growth regulators (Kinetin, Gibberellic Acid GA3) on bread wheat (Triticum aestivum L.) (Cham 6) emergence and seedling growth under normal (2.5 dS m-1) and saline (12 dS m-1) conditions were studied to determine their influence in increasing relative salt-tolerance. During emergence test, final emergence percentage, emergence reduction percentage and mean emergence time MET were significantly affected by the priming treatments. However, root and shoot length, fresh and dry weight of seedlings increased significantly at 25 ppm Kinetin treatment under both normal and saline conditions. All seed pretreatments decreased the electrolyte leakage of steep water as compared to that of non-primed seeds even after 12h of soaking. Seed soaking with 25 ppm Kinetin induced maximum decrease in electrolyte leakage, while an increase in electrolyte leakage was observed by 25, 50, or 100 ppm GA3 treatments. It is concluded that priming treatments reduced salinity injury, but the amelioration with 25 ppm Kinetin was better, in addition to the best results on seedling growth, fresh and dry weights under non-saline and saline conditions, whereas seed soaking with GA3 was not effective in inducing salt tolerance under the experimental conditions.